Diffuse Axonal Injury with Selective Involvement of the Corticospinal Tract: A Diffusion Tensor Imaging Case Study. Issue 4 (August 2014) - Tavanti, Francesca; Coppola, Valeria; Romano, Andrea; Beccia, Mario; Giuliani, Giorgia; Pierallini, Alberto; Bozzao, Alessandro
The identification of diffuse axonal injury (DAI) can be difficult, especially using conventional imaging (CT or MRI), which usually appears normal. Diffusion tensor imaging (DTI) is useful in identifying white matter abnormalities in patients with DAI. We describe the case of a 17-year-old female with severe closed head injury and right-side hemiparesis, studied with DTI and MR-tractography. In this case, DTI was useful to detect focal and diffuse signs of DAI.